Knowledge of PEP and PrEP among people living with HIV/aids in Brazil - Laelson Rochelle Milanês Sousa; Henrique Ciabotti Elias; Nilo Martinez Fernandes; Elucir Gir; Renata Karina Reis (BMC Public Health, 2021)
Abstract Background Pre-Exposure Prophylaxis (PrEP) and Post-Exposure Prophylaxis (PEP) are key to preventing sexual transmission of HIV, whose sexual partners are at high risk of acquiring HIV. We aimed to determine the factors associated with PrEP and PEP’s knowledge as secondary prevention among people living with HIV/AIDS. Method Cross-sectional analytical study carried out among people living with HIV/AIDS treated at five specialized services in the city of Ribeirão Preto, São Paulo, Brazil. Data were collected from July 2016 to July 2017. Individual interviews were conducted. We used multivariable logistic regression to determine factors associated with knowing PrEP and PEP. Results Of the 397 participants, 140 (35.26%) were heterosexual women aged 40 to 49 years (36.2%).Participants with less than 11 years of study (adjusted odds: 0.29; 95% CI: 0.13–0.60); who did not have a low viral load or did not know their viral load (adjusted odds: 0.29; 95% CI: 0.09–0.83) and those with casual partners (adjusted odds: 0.29; 95% CI: 0.09–0.83) were less likely to know about the PrEP. MSM (adjusted odds: 2.88; 95% CI: 1.59–5.3) and those who used alcohol during sexual intercourse (adjusted odds: 1.7; 95% CI: 1.0–2.8) were more likely to know about the PEP. Conclusions The knowledge about PEP and PrEP is low in Brazil. This may undermine secondary prevention efforts. Educational interventions to raise awareness of these prevention methods are needed among people living with HIV and who have HIV-negative sexual partners.